Pelaporan Keuangan Digital untuk UMKM: Membuka Akses Pembiayaan untuk Mendukung SDG 8 - Etty Gurendrawati; Muhammad Yusuf; Surya Anugrah; Unggul Purwohedi; Zakiyyah Riris Merbaka; Susan Fahirah; Yusuf Syaifulloh (Jurnal Abdi Masyarakat Nusantara, 2026)
This community service program aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) by implementing a digital financial reporting system (DFR), thereby expanding access to financing and supporting the achievement of Sustainable Development Goal (SDG) 8, specifically inclusive and sustainable economic growth. The main problems of MSMEs in Bulak Village, Indramayu Regency are low financial literacy and limited access to financial institutions due to unstandardized and lack of transparency in financial reports. This program is implemented through a Participatory Action Research (PAR) approach with stages of socialization, training, technology implementation, mentoring, and continuous evaluation of MSMEs in Bulak Village, Indramayu. This service utilizes the POS-aksi application, commonly used by MSMEs, in a simulation that prepares artificial intelligence-based financial reports. The results of the activity showed that 80% of MSMEs were able to operate the digital reporting application independently, and 46% successfully applied for formal financing using digital financial reports. This activity not only improves managerial capacity and financial transparency but also empowers students through the implementation of the Independent Learning Campus (MBKM). Thus, DFR is a strategic solution to strengthen the competitiveness of MSMEs and encourage economic growth based on digital inclusion.